American Studies in the Shadow of Orientalism. (2nd October 2015) - Soliman, Mounira
Abstract : The introduction of American literature in departments of English at Egyptian state-funded universities in 1959 coincided with the rising role of the US as a global power post World War II, its overtly imperial interests in the Middle East and the Arab World, and its support for the State of Israel. It became necessary then to engage with the US. This essay examines the fledgling attempts to develop American literature curricula into programs of American studies. It examines the neo-imperialist setup that gave rise to these attempts, and shows how public diplomacy initiatives which used American studies to propagate for American exceptionalism negatively influenced the development of these programs into academic platforms that engage critically with the US. The essay focuses on the case of the English Department at Cairo University, and attempts to read its history with American studies within the framework of transnationalism. It questions the term transnational, the relationship between US. And non US-based Americanists, the nature of their scholarship, and their contribution to reshaping the field of American Studies.